Naturally Occurring ‘enzyme only’ Anti-E antibody: A Rare Occurrence - Yousuf, Rabeya; Thalith, Nor Fadzliana Abdullah; Loong, Tang Yee; Leong, Chooi Fun (Bangladesh Journal of Medical Science, 2019)
Naturally occurring anti-E, present without obvious antigenic stimulation is a rare occurrence of red cell antibody of the Rh blood group system. It is mentioned that such naturally occurring anti-E react only with enzyme modified E-positive red cells. This case report describes a rare case of naturally occurring anti-E in a patient with autoimmune haemolytic anaemia (AIHA). Bangladesh Journal of Medical Science Vol.18(4) 2019 p.818-819